Mathematical description of the information security of mobile objects - Vilskyi, H. B.; Nadych, M .M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The principles of the mathematical description of the information security of mobile objects are considered in the paper. The possibility of applying mathematical methods to analyze the state of information security of mobile objects is shown.